B8 2018_VECEREK.pdf - Gill, Philip (Cranfield University, 2023)
STUDY OF NITROCELLULOSE SELF-IGNITION TEMPERATURE Petra L-oudová, Jiří Schejbal, Jaroslav Štěpán, Oldřich Večerek - SYNTHESIA, a. s. - Czech Republic
Keywords: 'nitrocellulose'